AB0528 ANALYSIS OF THE CASES OF 33 SLE PATIENTS THAT NECESSITATED CARDIOVASCULAR SURGERY. (June 2019) - Kawamoto, Toshio; Matsushita, Satoshi; Amano, Hirofumi; Minowa, Kentaro; Yoshida, Mai; Matsushita, Masakazu; Yamaji, Ken; Amano, Atsushi; Tamura, Naoto
Abstract : Background: In SLE, immune complexes are overproduced and deposited in tissues where they ultimately cause damage. The immunocomplexes, which are deposited in the myocardium, blood vessels and atrioventricular valves, have been suggested to cause damage to the relevant tissues, but it remains unclear in which cases tissue damage progresses to a point that surgical treatment is required. Objectives: The purpose of our study was to classify heart diseases into valvular heart diseases (V), ischemic heart diseases (I) and aortic aneurysms (A), to compare each class in terms of the correlation between the activity of SLE and the progression and exacerbation of heart disease, and in the future, to use the features of the correlations to carry out the prevention and treatment of heart diseases complicating SLE. Methods: Between the years 2012 and 2018, a total of 2852 patients diagnosed with SLE were admitted to our hospital, and 33 had heart surgery; however, 2 patients with infective endocarditis and one patient, who had not been diagnosed with SLE before surgery, were excluded from the study, therefore 30 cases were examined. Comparative studies were also carried out to examine the association between the levels of various autoantibodies and IgG and the onset of heart disease, the association between the total administered doses of steroids, the concomitant use of immunosuppressants as well as the association between DNA antibodies and complement. Results: At the time of the surgical treatment of the heart diseases, the mean duration of illness was 25.4 years, and the age was V vs. I vs. A=56.7 (44-79, median value: 56.2) vs. 55.1 (34-72, median value: 57.0) vs. 63.2 (41-78, median value: 65.5), showing that the age tended to be higher in the A group. The integrated value of the duration of illness and the level of anti-DNA antibodies, which served an index of activity, was calculated, and the findings revealed that V vs. I vs. A was (14020 vs. 32966 vs. 29444), showing that the values tended to be slightly lower in valvular heart diseases. As for antiphospholipid antibodies, the rate of positivity of either CLβ2GPI or anti-CL antibodies or LA was as follows: V vs. I vs. A (58% vs. 28% vs. 33%), showing that the rate tended to be higher in valvular heart diseases and that anti-CL antibody-positive patients were particularly higher in number among those with valvular heart diseases (V). The maximum preoperative levels of IgG were as follows: V vs. I vs. A (2803 vs. 1889 vs. 1708), which showed that the levels were higher with valvular heart diseases (V); those of SS-A antibodies were as follows: (36% vs. 43% vs. 42%), which showed high positive rates in all cases; and RNP antibody-positivity rates were as follows: (9% vs. 29% vs. 25%), and were relatively lower in valvular heart diseases (V). Regarding the medical treatment, the total administered doses of steroids were (25g vs. 39g vs. 63g) and tended to be lower in valvular heart diseases (V); use of immunosuppressants was found in 5 of 30 patients (16%); and concomitant use of both was particularly low in valvular heart diseases (V) as it accounted for only one case. Conclusion: Our study findings suggested that in SLE patients, prolonged duration of illness, positivity of SS-A antibodies and the absence of intake of immunosuppressants were highly likely to lead to cardiovascular diseases that need surgical treatment. Low integrated DNA antibody levels and the absence of concomitant use of immunosuppresants, despite high levels of IgG and the positivity of SS-A antibodies and anti-CL antibodies, might be risk factors for valvular heart diseases necessitating surgical treatment. References: [1] Yasuhiro Sakaguti, et al. Journal of Cardiology. 1995;25:181-188 [2] Stephane Zuily, et al. Curr Rheumatol Rep (2013) 15:320 [3] Zawadowski GM, et al. Lupus. 2012;21(13):1378-84 Disclosure of Interests: Toshio Kawamoto: None declared, Satoshi Matsushita: None declared, Hirofumi Amano: None declared, Kentaro Minowa: None declared, Mai Yoshida: None declared, Masakazu Matsushita: None declared, Ken Yamaji: None declared, Atsushi Amano: None declared, Naoto Tamura Grant/research support from: Astellas Pharma Inc., Asahi Kasei Pharma, AYUMI Pharmaceutical Co., Chugai Pharmaceutical Co. LTD, Eisai Inc., :Takeda Pharmaceutical Company Ltd., Speakers bureau: Janssen Pharmaceutical K.K., Bristol-Myers Squibb K.K., :Mitsubishi Tanabe Pharma Co.